ANALISIS PENGARUH RASIO KEUANGANDAN EVA TERHADAP HARGA SAHAM BANK - Rizal Silalahi (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Economic Value Added (EVA) has received a lot of recognition as a measure of predictionof share price. While the measure has been widely used for the purpose all over the world, manyresearch studies have appeared to examine variety of issues related to EVA. An attempt hasbeen made in this paper to call EVA-based analysis for the Indonesian Banking Industry. ASample of 10 public sector banks listed in Indonesia Stock Exchange has been selected. Thefinancial data of these sample units for four years, 2008-2011, have been used for the analysisand comparison. Equity approach has been followed to compute EVA. Economic Value Added(EVA) is now being considered as an important management tool across the banking world formeasuring and rewarding performance inside the bank. Most of the banks measure performancewith accounting profits which are often seriously measure of profitability. EVA is anothermeasure of profitability. Unlike accounting profits such as ROA, ROE, NPM, DER, EVAindicates the value to what extent created by management or agent for shareholders. This paperaims to analyze banks' performance through financial ratio and EVA. For this purpose, EVAhas been calculated taking certain assumptions as to the cost of equity and operational profitadjustments. A rank of regression coefficient between Share Price and different criteriaindicates the decreasing rank from high to low under 'Return on Asset', 'Debt to Equity','Economic Value Added' and 'Net Profit Margin'.